SUHU DARI LUAR TANGKI MUATAN MEMPENGARUHI PROSES MEMUAT DI LPG / C. LADY HILDE - Bintang Dwi Prayogo; Samsul Huda; Tri Kismantoro (Politeknik Ilmu Pelayaran Semarang, 2018)
The background of the writing of this study because the freight is often encounteredsome obstacles gas which is then encapsulated in a few issues, while the problemsencountered, among others, how is the role of the temperature outside propane tank in theloading process and any attempt to do when the temperature outside is different tanks withthe temperature in the cargo tank. In this study using qualitative methods, the research aimsto explain the phenomenon of the deepest data collection. This study does not give priority topopulation size or sampling, even a very limited sampling. If the data collected has beenprofound and could explain the phenomenon under study, then no need to look for othersampling. Qualitative research is more pressing on the issue of depth (quality) of data, notthe number (quantity) of data.It can be concluded that the change in temperature outside thevessel can greatly affect the handling of loading and unloading activities, especially in thecourse of loading, at which time the temperature outside is very cold or heat can affect thecondition of the cargo and the tank.